Cost of introducing and delivering RTS, S/AS01 malaria vaccine within the malaria vaccine implementation program. Issue 8 (17th February 2023) - Baral, Ranju; Levin, Ann; Odero, Chris; Pecenka, Clint; Tanko Bawa, John; Antwi-Agyei, Kwadwo Odei; Amponsa-Achaino, Kwame; Chisema, Mike Nenani; Eddah Jalango, Rose; Mkisi, Rouden; Gordon, Scott; Morgan, Winthrop; et al.
Abstract: Background: The World Health Organization (WHO) recommended widespread use of the RTS, S/AS01 (RTS, S) malaria vaccine among children residing in regions of moderate to high malaria transmission. This recommendation is informed by RTS, S evidence, including findings from the pilot rollout of the vaccine in Ghana, Kenya, and Malawi. This study estimates the incremental costs of introducing and delivering the malaria vaccine within routine immunization programs in the context of malaria vaccine pilot introduction, to help inform decision-making. Methods: An activity-based, retrospective costing was conducted from the governments' perspective. Vaccine introduction and delivery costs supported by the donors during the pilot introduction were attributed as costs to the governments under routine implementation. Detailed resource use data were extracted from the pilot program expenditure and activity reports for 2019–2021. Primary data from representative health facilities were collected to inform recurrent operational and service delivery costs. Costs were categorized as introduction or recurrent costs. Both financial and economic costs were estimated and reported in 2020 USD. The cost of donated vaccine doses was evaluated at 2, 5 and 10 per dose and included in the economic cost estimates. Financial costs include the procurement add on costs for the donated vaccines and immunization supplies, along with other direct expenses. Findings: At a vaccine price of 5 per dose, the incremental cost per dose administered across countries ranges from 2.30 to 3.01 (financial), and 8.28 to 10.29 (economic). The non-vaccine cost of delivery ranges between 1.04 and 2.46 (financial) and 1.52 and 4.62 (economic), by country. Considering only recurrent costs, the non-vaccine cost of delivery per dose ranges between 0.29 and 0.89 (financial) and 0.59 and 2.29 (economic), by country. Introduction costs constitute between 33% and 71% of total financial costs. Commodity and procurement add-on costs are the main cost drivers of total cost across countries. Incremental resource needs for implementation are dependent on country's baseline immunization program capacity constraints. Interpretation: The financial costs of introducing RTS, S are comparable with costs of introducing other new vaccines. Country resource requirements for malaria vaccine introduction are most influenced by vaccine price and potential donor funding for vaccine purchases and introduction support.